The Correlation between Family Support with the Quality of Life of Patients with Diabetes Mellitus - Nilla Retnowati; Prijono Satyabakti (Universitas Airlangga, 2015)
Diabetes Mellitus (DM) is a disease that will accompany a lifetime and require long-term care so that it can reduce the quality of life of sufferers. This study aims to analyze the relationship between family support and the quality of life of people with diabetes mellitus. This type of research is observational analytic with a cross-sectional study design. The study population was all people with diabetes mellitus who visited the Public health center (PHC) of Tanah Kalikedinding in January - March 2014. Patients were diagnosed with diabetes mellitus through laboratory tests using venous plasma blood serum. The size of the study sample is 45 respondents who were selected by simple random sampling. The variables studied included family support, respondent characteristics (age, sex, level of education, income, marital status, and employment status), duration of DM, complications of DM, and quality of life. Chi-square test results with continued Fisher's exact test showed variables that were significantly related to quality of life including family support (p = 0,000), level of education (p = 0.039), income (p = 0.034), marital status (p = 0.003 ) and DM complications (p = 0.007). The Mantel-Haenszel test results show that all the variables studied were confounding on the relationship of family support to quality of life. The confounding variable which has the biggest contribution is DM complications. The conclusion is that family support is significantly related to the quality of life of people with diabetes mellitus at the PHC of Tanah Kalikedinding. PHC is expected to be able to carry out educational and health promotion programs for people with diabetes mellitus and their families to improve patients’ quality of life.